2012
DOI: 10.1017/s1751731111001418
|View full text |Cite
|
Sign up to set email alerts
|

Authentication of beef production systems using a metabolomic-based approach

Abstract: There is a need for new, non-invasive, rapid and reliable analytical methodologies that can easily be implemented and used for authentication of cattle production systems and the meat derived from them. Easily quantifiable markers could strengthen the current tracing methods for beef authentication. This study investigated the use of a nuclear magnetic resonance-based metabolomic approach as a tool to authenticate beef on the basis of the pre-slaughter production system. Urine and muscle samples were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 36 publications
(35 reference statements)
0
16
0
Order By: Relevance
“…Geographic differences may also contain the production systems of animals. A study aiming to discriminate the pre-slaughter production system was able to distinguish differences between 1-year cattle fed with barley-based concentrate indoors and with pasture feeding outdoors, using NMR metabolomics followed by PLS-DA, analyzing the longissimus dorsi (LD) muscle [68]. The results suggested that NMR approach is suitable for authentication of cattle production history.…”
Section: Authenticationmentioning
confidence: 99%
“…Geographic differences may also contain the production systems of animals. A study aiming to discriminate the pre-slaughter production system was able to distinguish differences between 1-year cattle fed with barley-based concentrate indoors and with pasture feeding outdoors, using NMR metabolomics followed by PLS-DA, analyzing the longissimus dorsi (LD) muscle [68]. The results suggested that NMR approach is suitable for authentication of cattle production history.…”
Section: Authenticationmentioning
confidence: 99%
“…These laboratory methods have measured the fatty acid composition of muscle and subcutaneous fat and the concentration of β‐carotene. [ 8–13 ] The disadvantage of utilising these methods is the inability to perform these tests in a processing facility, as they require extensive sample preparation. These methods, however, can provide a reference test that can be utilised to evaluate the effectiveness of new technologies, which are able to provide rapid results.…”
Section: Introductionmentioning
confidence: 99%
“…Like other “Omics”, it has been applied in a broad range of applications, such as agriculture, environment monitoring, and medicine [15-17]. In recent years, metabolomics has been successfully applied in disease diagnosis [18].…”
Section: Introductionmentioning
confidence: 99%